2019
DOI: 10.1016/j.cnp.2019.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Auditory processing disorder evaluations and cognitive profiles of children with specific learning disorder

Abstract: Highlights Children with altered auditory processing exhibit a specific cognitive profile. Lower verbal and spatial reasoning performance are associated with altered auditory processing. Children with specific learning disorder should undergo a complete multimodal examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
1
4
0
4
Order By: Relevance
“…Considerable research supports the view that many dyslexics also have auditory processing deficits (Halliday et al, 2017, p. 140). It is estimated that 10% of the general population has an abnormal range for learning skills, of which 37% of that population will have dyslexia and 46% will be co-morbid with APD (Cunha et al, 2019, p. 120, citing Dawes & Bishop, 2010. Recent research found that forty percent of children with dyslexia have another diagnosed neurological disorder (Snowling et al, 2020, p. 505).…”
Section: Does Dyslexia or Apd Come First?mentioning
confidence: 99%
“…Considerable research supports the view that many dyslexics also have auditory processing deficits (Halliday et al, 2017, p. 140). It is estimated that 10% of the general population has an abnormal range for learning skills, of which 37% of that population will have dyslexia and 46% will be co-morbid with APD (Cunha et al, 2019, p. 120, citing Dawes & Bishop, 2010. Recent research found that forty percent of children with dyslexia have another diagnosed neurological disorder (Snowling et al, 2020, p. 505).…”
Section: Does Dyslexia or Apd Come First?mentioning
confidence: 99%
“…Estudos apontam que a disfunção auditiva periférica, acompanhada ou não de história de otite média secretora na primeira infância pode resultar em imaturidade no desenvolvimento de vias auditivas e habilidades auditivas centrais (2,3) . Além disso, alterações nas habilidades auditivas podem interferir no processo de aprendizagem e desenvolvimento da criança, devido ao fato de haver interdependência com as funções cognitivas superiores, tais como linguagem, memória e atenção (4,5) . A ocorrência do TPAC na criança em idade escolar pode coexistir com outros transtornos, como o Transtorno de Déficit de Atenção e Hiperatividade (TDAH), Transtornos do Desenvolvimento da Linguagem, Dislexia, entre outros (6,7) .…”
Section: Introductionunclassified
“…Essas queixas acarretam dificuldades que, na maioria dos casos, manifestam-se a partir de um baixo desempenho acadêmico (9) . Estudos demonstram associação entre a presença do TPAC e transtornos específicos de aprendizagem (5) , principalmente relacionado aos processos de aquisição da leitura e escrita e cálculos matemáticos, bem como déficits fonológicos (10) e percepção da fala, incluindo aspectos suprassegmentais do discurso (11) .…”
Section: Introductionunclassified
“…Studies show peripheral auditory dysfunction-with or without a history of secretory otitis media in early childhood-can result in immature auditory pathways and central auditory skills (2,3) . In addition, alterations in auditory skills can affect a child's learning and development processes, due to an interdependence with higher cognitive functions, such as language, memory, and attention (4,5) . CAPD in school-age children can coexist with other disorders, such as attention deficit hyperactivity disorder (ADHD), language development disorders, dyslexia, among others (6,7) .…”
Section: Introductionmentioning
confidence: 99%